Linguistic difficulties in the learning of foreign languages - Uvarova, Maria A. (Studia Ecologiae et Bioethicae, 2017)
The paper describes linguistic and cultural-linguistic difficulties that one has to overcome when learning a foreign language. These difficulties arise not just from the differences in phonetics, grammar or syntax, but also from the differences in culture, history, and the way of life between the native speakers and the student. Some difficulties are obvious, others are not. But the key to mastering a foreign language is diligent studying, not just the language itself, but also all aspects of culture and history of the people speaking it on the basis of a good knowledge of one’s own language and culture.